The effects of recidivism on criminal enforcement - Cananéa , Lilian Frassinetti Correia; Vilar, Peterson Rodrigues Macêdo (Seven Editora, 2024)
The main purpose of the article is to analyze the effects of recidivism in the context of penal execution, when prison task forces are carried out. In order to develop the study, the starting point will be the understanding of the functioning of the task forces and, then, the legal analysis of the issues related to recidivism. The general objective of the study is to analyze what are the effects of recidivism on penal execution and, in order to achieve the desired proposal, the following are the following specific objectives: to understand the functioning of a prison task force; reflect on the importance of the prison task force; understand the position of the STJ with regard to the process of calculating penalties for cases of recidivism. To this end, as a technical procedure, a bibliographic, descriptive research and deductive approach method will be carried out. DOI:https://doi.org/10.56238/sevened2024.026-029